2020
DOI: 10.3389/fbioe.2020.00128
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Single-Gene and Gene Family Editing in the Apicomplexan Parasite Eimeria tenella Using CRISPR-Cas9

Abstract: Eimeria species are pathogenic protozoa with a wide range of hosts and the cause of poultry coccidiosis, which results in huge economic losses to the poultry industry. These parasites encode a genome of ∼8000 genes that control a highly coordinated life cycle of asexual replication and sexual differentiation, transmission, and virulence. However, the function and physiological importance of the large majority of these genes remain unknown mostly due to the lack of tools for systematic analysis of gene function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Now we have achieved transgenic E. acervulina with a fluorescent rate of more than 95% by using only fluorescent protein (EYFP) as a screening marker (Yu et al, unpublished data). At the same time, our laboratory has also achieved CRISPR/Cas9 gene knockout on Eimeria [ 36 , 37 ]. Therefore, after obtaining a stable transgenic E. acervulina line, we can use a gene-editing system to knock out the other selection markers like YFP, RFP, and DHFR-TS.…”
Section: Discussionmentioning
confidence: 99%
“…Now we have achieved transgenic E. acervulina with a fluorescent rate of more than 95% by using only fluorescent protein (EYFP) as a screening marker (Yu et al, unpublished data). At the same time, our laboratory has also achieved CRISPR/Cas9 gene knockout on Eimeria [ 36 , 37 ]. Therefore, after obtaining a stable transgenic E. acervulina line, we can use a gene-editing system to knock out the other selection markers like YFP, RFP, and DHFR-TS.…”
Section: Discussionmentioning
confidence: 99%
“…The programs EO100, EH100, and EO114 in Lonza 4D-Nucleofector have higher transfection efficiency than others ( Supplementary Figure S6 ). So far, there are two reported genome editing studies ( Hu et al, 2020 ; Tang et al, 2020 ). We summarized it as Supplementary Table S3 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed for optimization of the transgenic promoters, fluorescent reporter genes, fusion strategy, and selection for enrichment of positive transformants ( Clark et al, 2008 ; Hanig et al, 2012 ; Tang et al, 2016 ; Pastor-Fernandez et al, 2019 ), i.e., using the selection marker dihydrofolate reductase–thymidylate synthase ( DHFR ) gene ( Liu et al, 2008 ). Due to the lack of a method providing a continuous culture of Eimeria at one stage as Toxoplasma , no genome editing techniques have been reported until the past year ( Hu et al, 2020 ; Tang et al, 2020 ). It was reported that an E. tenella parasite strain harboring eCas9 expression would facilitate gene manipulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional analysis of the pre-sexual stages of E. tenella revealed that ApiAP2 expression profile changes during pre-sexual development ( Su et al., 2017 ). Individual deletion of 10 out of 33 ApiAP2 factors was successful in a screening performed in sporozoites of E. tenella ( Hu et al., 2020 ). This finding indicates that these 10 ApiAP2 are likely dispensable in E. tenella .…”
Section: Sexual Commitment and Differentiation In Coccidiamentioning
confidence: 99%